Pattern of Psychiatric Referral in a Tertiary Care Hospital in Bangladesh (Bangladesh Journal of Medicine, 2020)
Introduction: Consultation-liaison Psychiatry (CLP) is the study, practice and teaching of the relationbetween medical and psychiatric disorders.Aim of the study: The aim of this study is to find out the referring department, reason for consultation,common psychiatric comorbidities and sociodemographic of the referred patients to psychiatrydepartment from the other departments of Bangabandhu Sheikh Mujib Medical University of Dhaka.Methodology: This cross-sectional study was carried out from May 2018 to February 2020. Patientsreferred from different inpatient departments every Thursday were taken as study population.Psychiatric diagnoses of the patients were assigned by the consultant psychiatrist as per DSM-5criteria. Semi structured questionnaire was used to collect socio-demographic data.Results: Among the referred patients (n= 89) 56% were female; 63% were aged between 19-59years; 65% were married; 58% were from urban background and 51% studied up to higher secondary.More than half of the patients were referred from different branches of Medicine (68%). Referral fromInternal Medicine was 14.6%, Rheumatology 13.5%, Neurology and Nephrology 10% respectively.The rest were from the branches of pediatrics, surgery and gynecology. Most common psychiatricdisorder was Major Depressive Disorder (37%) followed by Obsessive-Compulsive Disorder (17%)and Delirium (10.11%). 15% patient received no psychiatric diagnosis.Conclusion: Psychiatric comorbidities in general medical illness are very common. CLP provides anopportunity to improve health outcomes for inpatients and reduce burden on the healthcare system.Bangladesh J Medicine July 2020; 31(2) :76-80